Industrial innovation and parallel accounting developments - Sweeting, R.C (Technovation)
Via an ongoing research programme, the authors present and discuss changes and developments in accounting techniques in an equally changing manufacturing environment. They stress the importance of top management involvement and support in accounting innovations with extended use of parallel rather than sequential processes of development.